2011
DOI: 10.4103/1658-354x.84098
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the ratio of patient's height to thyromental distance with the modified Mallampati and the upper lip bite test in predicting difficult laryngoscopy

Abstract: Background:The aim of the present study was to compare the ability to predict difficult visualization of the larynx from the following preoperative airway predictive indices, in isolation and combination: modified Mallampati test (MMT), the ratio of height to thyromental distance (RHTMD) and the Upper-Lip-Bite test (ULBT).Methods:We collected data on 603 consecutive patients scheduled for elective surgery under general anesthesia requiring endotracheal intubation and then evaluated all three factors before sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…The diagnostic accuracy of this test is also less among all the other tests. Safavi et al [27] in their study on 603 adult subjects for comparing ULBT, RHTMD with MMT for difficult laryngoscopy and intubation found that RHTMD has some limitations. It depends on accurate measurement of patient's TMD and height that lessens simplicity of this method.…”
Section: Ratio Of Height To Thyromental Distance (Rhtmd)mentioning
confidence: 99%
“…The diagnostic accuracy of this test is also less among all the other tests. Safavi et al [27] in their study on 603 adult subjects for comparing ULBT, RHTMD with MMT for difficult laryngoscopy and intubation found that RHTMD has some limitations. It depends on accurate measurement of patient's TMD and height that lessens simplicity of this method.…”
Section: Ratio Of Height To Thyromental Distance (Rhtmd)mentioning
confidence: 99%
“…RHTMD measurement has high sensitivity than other tests and is sufficiently sensitive to detect possible difficulties with laryngoscopy and intubation. [ 20 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…The ratio was calculated [5] . RHTMD: Thyromental distance was measured from the bony point of the mentum while the head was fully extended with close mouth.Then the ratio of height to TMD was calculated [7] .…”
Section: Methodsmentioning
confidence: 99%
“…Recently "i" studies have shown that NC/TMD is a sensitive test to predict diicult airway in general population [5] and obstetrics [6] . Also RHTMD (Ratio of Height to Thyromental Distance) that has high sensitivity, is suiciently sensitive to detect possible diiculties with laryngoscopy and intubation in obstetrics(AUC = 0.627, 95% CI, 0.589-0.664) [7] . The modiied Mallampati classiication has poor prognostic value [2,[6][7][8] in many studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation